Kajian penggunaan tagetes erecta dan tagetes patula untuk mengendalikan nematoda parasitik pada tanaman pisang. (Studies on the effect of tagetes erecta and tagetes patula for controlling plant parasitic nematodes on ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1993)
An experiment to study the effect of Tagetes erecta L. and T.. patula. in controlling plant parasitic nematodes on banana was conducted at the Banana Collection Garden, Agricultural Extension Service for Food Crops, Yogyakarta. Banana variety used in this experiment was "Pisang Raja" and the plant was intercropped with both Tagetes plants. Plots in the experiment were arranged in Randomized Completely Block Design with three factors and six blocks. Those factors were banana intercropped with six rows of T. erecta, banana intercropped with six rows of .T. patula, and banana with no intercropping. Observations were done on the number of plant parasitic nematodes in the soil on each plot before planting, population number in the soil and banana roots on each plot at 30, 60, 90 and 120 days after planting